1. Peran Trauma dan Memori dalam Politik Luar Negeri: Studi Kasus Kebijakan Jerman Menerima Pengungsi Suriah 2011-2015 - Ratna Kusuma Wardhani; Reni Windiani; Mohamad Rosyidin (International Relations, Faculty of Social and Political Sciences, Universitas Diponegoro, 2017)
The flow of refugees arriving in the Europe Union has made the majority of European countries overwhelmed except for Germany that implements the Open-Door Policy under which the refugees are wholeheartedly welcome especially those coming from Syria. This study aims to analyze why Germany prefers to take a rather unique and unusual approach toward refugees by receiving larger number of Syrian refugees compared to other European states. This study applies the concept of memory and trauma in world politics to explain said phenomena. As widely believed, trauma and memory are two important factors that could affect the pattern of state policies. Written in qualitative approach, this study argues that the open door policy of Germany has been mainly driven by some human tragedy that took place within Germany in the past, namely Holocaust. The conclusion of this study is that the trauma of the Holocaust has created a memory that affects contemporary German politics and its political decision thereafter including in this case, the Open Door Policy.